Climate ethics: the theatre of the oppressed meets ethics roundtables - Anthony, Raymond (Revista Española de Desarrollo y Cooperación, 2023)
Role-playing techniques encourage doing philosophy in the spirit of standpoint epistemology. Interactive performance theatre and ethics roundtable enhance problem-based learning, communication skills, civic engagement and stakeholder analysis. These techniques were used to accentuate deliberation around climate change and food ethics issues with particular emphasis on the needs of the most vulnerable Alaskans.